The Scholarship of Teaching and Learning as a subversive activity - Boose, David L.; Hutchings, Pat (Teaching and Learning Inquiry, 2016)
One of the most serious challenges facing higher education today is the erosion of academic culture—a declining sense that faculty form a community whose members reflect, deliberate, and make decisions together in the name of a shared educational vision. Our experience with Gonzaga University’s Scholarship of Teaching and Learning (SoTL) Initiative suggests that SoTL can be a powerful counter force to this erosion. What became increasingly evident as the initiative unfolded was that its most important result was the creation of a kind of alternative academic community that stands in opposition to many of the dis-integrative, disempowering forces at work in higher education. The scholarly examination of practice, done in a collaborative context, changed participants’ perceptions of learning, of themselves as teachers, and of the larger endeavor of which they are a part. Thus, we came to see the SoTL initiative as a subversive activity in the sense used by Neil Postman and Charles Weingartner in their 1969 book, Teaching as a Subversive Activity: one that invites critical questions about education’s purposes, practices, and underlying assumptions, and in so doing reanimates core values.